Nutrition now - Brown, Judith E. (Australia : Wadsworth Cengage Learning, 2014)
NUTRITION NOW introduces non-major students to the science of nutrition while engaging them through active learning exercises and applied, real-world examples. This text's unique modular format (33 units) helps students focus on critical content by organizing the material into smaller sections and provides instructors the flexibility to choose which units to cover and modify the order to meet course goals and objectives. This evidence-based text uses a direct, student-friendly writing style that makes content approachable, but not oversimplified. The emphasis on active learning and critical thinking allows instructors to design an interactive environment regardless of class size or format (in classroom or online). NUTRITION NOW offers a flexible option to meet your course needs that will get your students excited about the science of nutrition.
Part I: NUTRITION BASICS AND TOOLS FOR PLANNING.1. Key Nutrition Concepts and Terms.2. The Inside Story about Nutrition and Health.3. Ways of Knowing about Nutrition.4. Understanding Food and Nutrition Labels.5. Nutrition, Attitudes, and Behavior.6. Healthy Diets, the Dietary Guidelines, MyPlate, and More.Part II: FOOD IN THE BODY.7. How the Body Uses Food: Digestion and Absorption.8. Calories! Food, Energy, and Energy Balance.9. Obesity to Underweight: The Highs and Lows of Weight Status.10. Weight Control: The Myths and Realities.11. Disordered Eating: Anorexia Nervosa, Bulimia, and Pica.Part III: THE MACRONUTRIENTS: CARBOHYDRATES.12. Useful Facts about Sugars, Starches, and Fiber.13. Diabetes Now.14. Alcohol: The Positives and Negatives.Part IV: THE MACRONUTRIENTS: PROTEIN.15. Proteins and Amino Acids.16. Vegetarian Diets.17. Food Allergies and Intolerances.Part V: THE MACRONUTRIENTS: FAT.18. Fats and Cholesterol in Health. 19. Nutrition and Heart Disease.Part VI: VITAMINS, MINERALS, AND SUPERFOODS.20. Vitamins and Your Health.21. Phytochemicals.22. Diet and Cancer.23. Good Things to Know About Minerals.24. Dietary Supplements and Functional Foods.25. Water Is an Essential Nutrient.26. Nutrition-Gene Interactions in Health and Disease.Part VII: NUTRITION AND FITNESS.27. Nutrition and Physical Fitness for Everyone.28. Nutrition and Physical Performance.Part VIII: NUTRITION IN THE LIFE CYCLE.29. Good Nutrition for Life: Pregnancy, Breastfeeding, and Infancy.30. Nutrition for the Growing Years: Childhood through Adolescence.31. Nutrition and Health Maintenance for Adults of All Ages.Part IX: GLOBAL CONSIDERATIONS.32. The Multiple Dimensions of Food Safety.33. Aspects of Global Nutrition.
Includes bibliographical references and index.
Keywords: NUTRITION